Answer:
B. F(1) = -11
F(n) = f(n-1) + 3; for n = 2,3,4...
Explanation:
The given sequence is -11, -8, -5,-2,-1,...
The first term is f(1)=-8 and the common difference is
![d = - 8 - - 11 = 3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nwwjb80qdjn997ewyngpuohdaoazg7h4mj.png)
The recursive definition of this sequence is given by:
![f(n) = f(n - 1) + d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/opmkc5zyxgz2idckfgyzqv4n4pq0k16zw7.png)
This implies that:
![f(n) = f(n - 1) +3 \: where \: f(1) = - 11](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xu8frc9j1oazpmq5sxs640p53luquwy0c7.png)
and n=2,3,4,5,...
The second choice is correct